The Rise of the Dutch Republic $1 (BVolume 23: 1576s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 23: 1576" by John Lothrop Motley is a historical account written during the mid-19th century. The book delves into the complex political and social turmoil of the Netherlands during a pivotal time in their struggle against Spanish rule. It explores key figures, most notably the Prince of Orange, and the various factions in play as the provinces grappled with issues of governance, foreign influence, and religious persecution. The opening of this volume introduces a critical juncture in the Dutch struggle for independence with the sudden death of Requesens, a Spanish governor, creating a power vacuum that the Prince of Orange seeks to exploit. It details the subsequent assumption of power by the State Council at Brussels, the indecision in Madrid, and the burgeoning unity among the provinces in their mutual desire to expel foreign troops and maintain their rights. The narrative highlights the pervasive discontent among both the Spanish military and the Dutch populace, leading to acts of rebellion and strategic calls to arms led by the Prince, who rallies support from across the provinces. In this turbulent environment, themes of loyalty, national identity, and the fight for freedom take center stage, setting the tone for the conflicts and resolutions that follow. (This is an automatically generated summary.)s
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history